Hubungan Lingkungan, Sosial Budaya, Pengetahuan Serta Sikap Akseptor KB Tentang Kontrasepsi Suntik 3 Bulan Dengan Kepatuhan Kunjungan Ulang Di Pmb Yayah Asy’ariyah Desa Gunung Cupu - Yayah Asy’ariyah; Agus Santi Br Ginting; Fanni Hanifa (THE JOURNAL OF Mother and Child Health Concerns, 2022)
Backgrounds: Family planning is an action that helps individuals or married couples to get certain objectives, avoid unwanted births, get births that are wanted, regulate the interval between pregnancies and control the time of birth in a husband and wife relationship. The coverage of participants using contraceptives in Indonesia in 2017 with the number of couples of childbearing age as many as 48,536,690 participants; the most widely used contraception by family planning participants in Indonesia is the injectable contraceptive method. The failure of the injectable contraceptive method was caused by the acceptor's delay in re-injecting. Purpose: This study aims to determine the relationship between the socio-cultural environment, knowledge and attitudes of family planning acceptors about 3-month injectable contraception with re-visit compliance at PMB Yayah Asy'ariyah Gunung Cupu Village in 2022. Methods: This study used descriptive analytic with a cross sectional approach. The population of this study amounted to 30 acceptors of 3-month injectable contraception. Sampling technique using the total population. Results: The results showed that there was a significant relationship between socio-cultural and return-visit compliance, a p-value of 0.009 was obtained, knowledge and compliance with repeated visits obtained a p-value of 0.001, and there was no significant relationship between the environment and re-visit compliance, a P-value of 0.094 was obtained. Attitude with compliance with repeat visits obtained a p-value of 0.176. Conclusion: The socio-cultural factors and knowledge affect the compliance of repeat visits by 3-month injection contraception acceptors, while environmental factors and attitudes have no effect on adherence to 3-month injections contraception acceptor repeat visits. Suggestion: Respondents and their families are expected to be able to provide support to mothers in choosing, and determining the contraceptives to be used and the importance of compliance during repeat visits, so that the effectiveness of contraception can be maximized.   Keywords: Family Planning Acceptors; 3-month Injectable Contraception; Compliance.   Pendahuluan: KB adalah tindakan yang membantu individu atau pasangan suami istri untuk mendapatkan objektif tertentu, menghindari kelahiran yang tidak diinginkan, mendapatkan kelahiran yang memang diinginkan, mengatur interval di antara kehamilan dan mengontrol waktu saat kelahiran dalam hubungan suami istri. Cakupan peserta pengguna alat kontrasepsi di Indonesia pada tahun 2017 dengan jumlah pasangan usia subur (PUS) sebanyak 48.536.690 peserta, kontrasepsi yang paling banyak digunakan oleh peserta KB di Indonesia yaitu metode kontrasepsi suntik. Kegagalan dari metode kontrasepsi suntik disebabkan karena keterlambatan akseptor untuk melakukan penyuntikan ulang. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara Lingkungan Sosial Budaya, Pengetahuan Serta Sikap Akseptor KB Tentang Kontrasepsi Suntik 3 Bulan dengan Kepatuhan Kunjungan Ulang di PMB Yayah Asy’ariyah Desa Gunungcupu tahun 2022. Metode: Penelitian ini menggunakan deskriptif analitik dengan pendekatan cross sectional. Populasi penelitian ini berjumlah 30 orang akseptor KB suntik 3 bulan. Teknik pengambilan sampel dengan menggunakan total populasi. Hasil: Hasil penelitian menunjukan bahwa ada hubungan signifikan antara sosial budaya dengan kepatuhan kunjungan ulang diperoleh nilai P Value 0,009, pengetahuan dengan  kapatuhan kunjungan ulang diperoleh nilai P Value 0,001, serta tidak ada hubungan yang signifikan antara lingkungan dengan kepatuhan kunjungan ulang diperoleh nilai P Value 0,094, dan sikap dengan kapatuhan kunjungan ulang diperoleh nilai P Value 0,176. Simpulan: Faktor sosial budaya dan pengetahuan berpengaruh terhadap kepatuhan kunjungan ulang akseptor KB suntik 3bulan, sedangkan faktor lingkungan dan sikap tidak berpengaruh terhadap kepatuhan kunjungan ulang akseptor KB suntik 3 bulan. Saran: Responden dan keluarga diharapkan dapat memberikan dukungan kepada ibu dalam memilih, dan menentukan kontaspsi yang akan digunakan dan pentingnya kepatuhan saat kunjungan ulang, agar efektivitas kontasepsi dapat maksimal.